Muldfjælsplovens tidlige historie – Fra yngre romersk jernalder til middelalder - Agersnap Larsen, Lars (Kuml, 2015)
The early history of the mouldboard plough – from the Late Roman Iron Age to the Middle Ages Until quite recently, the introduction of the mouldboard plough to Denmark was seen as being closely linked to a new efficient Medieval cultivation system, the open-field system, which was considered to be the foundation for dynamic social changes evident in the area from c. AD 1000-1300. The open-field system is often explained in the context of a Medieval agricultural and technological revolution, whereby the mouldboard plough, ridge-and-furrow cultivation and crop rotation were introduced as a kind of package solution. Studies of Danish Medieval written sources suggest that these agrarian changes took place in AD 1000-1200, with use of the mouldboard plough consequently not being thought of as much older. Until the late 1990s, this idea was not contradicted by the significant body of evidence in the Danish archaeological record relating to the mouldboard plough, which in many ways is unique in a European perspective. Subsequently, new archaeological finds of well-preserved furrows made by a mouldboard plough have been discovered which clearly show that this implement was introduced to Denmark about 700-800 years earlier than previously thought, i.e. in the Late Roman Iron Age, c. AD 200-400. This challenges our understanding of the introduction of the mouldboard plough and the history of cultivation systems in Denmark prior to the Middle Ages and the evidence has therefore been subjected to new investigations. Archaeological finds of plough components The archaeological record contains the only known finds of wooden plough components such as the beam, sheath, sole and mouldboard, as well as finds of the coulter, draught chains and shares (fig. 1). These finds can be dated to the period from the Late Viking Age to the Late Middle Ages or Renaissance. The archaeological record, together with pictorial representations on frescoes and seals from Denmark, provides a relatively tangible picture of the plough as basically a quadrilateral construction with the mouldboard attached to the right side. How far back in time this plough construction was used is not known for sure, but it is possible that it was developed by farmers as far back as the Iron Age, possibly being best suited to the asymmetrical function of the plough. It is obviously unlikely that an implement which was used for more than 1500 years remained static and unchanged in every way. As a consequence, the possibility cannot be ruled out that other versions of the mouldboard plough, either simpler or more complex, have existed over time. Ploughing traces Archaeological investigations have unearthed several minor occurrences of fossil ploughing traces dated to between the Late Iron Age and the Middle Ages. These take the form of ridge-and-furrow systems, turned furrows and furrow strips possibly correlated with the plough (fig. 6). In the light of the traces found at Tating-Haferacker, St. Peter-Ording, Joldelund and Danevirke, it must be assumed that the mouldboard plough was known and used across larger parts of South Schleswig in the Late Roman Iron Age. It may be possible to show that the plough was used even further north Jutland at this time, as the ploughing traces found in Henneby may date from the Late Roman Iron Age rather than the Germanic Iron Age. Notwithstanding the uncertainty regarding Henneby, the traces from Dommerhaven in Ribe and Klinkerne (figs. 2 and 3) show that the plough was known and used in significant parts of western Jutland by the Late Germanic Iron Age at the latest. There are presently no ploughing traces from other parts of Denmark dating from this period, although the furrows found beneath the burial mound Grydehøj on Zealand could have been produced by this plough. Similarly, the traces dated to the Viking Age, found at Hedeby, Fjand, Viborg (fig. 4), Lindholm Høje and Löddeköpinge, show that the plough must have been known and used across significant parts of Jutland and in Scania before the end of the Viking Age. Early Middle Ages ploughing traces have been found at Filsø and some other locations in Jutland and on Funen, but so far no definite ploughing traces are known from Zealand and Scania. There are only a few localities with ploughing traces dating from the rest of the Middle Ages: Ringkøbing, Puggårdsgade in Ribe, Amrum and Südfall in the western part of Denmark. The traces found at Ulbjerg Klint are unlikely to be later than the 15th-16th centuries (fig. 5). At first sight, this review of the fossil ploughing traces can be broadly interpreted as showing that the introduction of the plough to Denmark was an extended process, which began in South Schleswig no later than the Late Roman Iron Age and continued into the western parts of Denmark no later than the Germanic Iron Age, and reached the remaining parts of Denmark no later than the Viking Age. The question is, however, whether the review has given a better basis for determining when and how the mouldboard plough became a regular implement in various parts of Denmark. All things considered, the archaeological record only shows where the conditions for preservation have been particularly good for these specific types of finds, and where excavators happen to have found turned furrows when carrying out archaeological investigations. In western Jutland, peaty/boggy soils and sand drift have given good conditions for the preservation of fossil turned furrows, while the same conditions seldom exist in other parts of Denmark. This is emphasised by the fact that the finds of turned furrows dating from the Middle Ages have almost exclusively been found in western Jutland, even though the plough is considered to have been common across most of Denmark at this time. Consequently, the absence of fossil turned furrows cannot be used as evidence of the plough not having been known and used in the area in question. It would therefore be irresponsible to make dogmatic unambiguous statements about regional variations in the introduction of the plough to Denmark. Rye cultivation as an indicator of the use of the plough The problem can be addressed indirectly by turning to another source material. Perhaps the the more widespread cultivation of rye may be used as an indicator of the presence of the plough in a given area. Rye, as known from historical times, does not make great demands as to the type of soil, but it does require that the soil has been loosened and is not waterlogged; surface water can also destroy the rye. The mouldboard plough has therefore been considered as a prerequisite for more widespread and systematic cultivation of rye, especially winter rye, on the wet northwest European lowlands. This is because the plough could efficiently loosen the soil and gather it into ridged strips, facilitating field drainage. General developments clearly show that, after a cautious start in Late Roman Iron Age, rye was found increasingly during the Germanic Iron Age and subsequent periods. It would be irresponsible to draw too far-reaching conclusions with respect to relations between rye and the plough. However, if we accept the idea of a connection between the mouldboard plough and the more widespread and systematic cultivation of rye – especially winter rye, then it is tempting to claim that the results of the present review reflect a form of agriculture in which the mouldboard plough was in use across most of Denmark during the Germanic Iron Age. Perspectives on the early introduction of the mouldboard plough The mouldboard plough is interesting in both an ecological and a socio-economic context, because it was of major significance for tillage and prompted a reorganisation of field structures that, with time, had a knock-on effect on the structures of settlements and properties. The idea of a technological revolution around AD 1000 acting as a catalyst for dynamic social changes is no longer tenable. The earlier dates now established for the mouldboard plough, the ridged strips and crop rotation clearly show that these significant agricultural prerequisites for a new and effective Medieval system of cultivation, the open-field system, were very well-known in Denmark before this form of agriculture took shape at the beginning of the Early Middle Ages, AD 1000-1200. There is, therefore, no reason to stick to the idea of a technological revolution at this time. The dynamic changes evident in the Middle Ages are, instead, more likely to be a consequence of a general economic expansion, which saw expression for example in an increase in new villages and an associated expansion of the cultivated landscape during the Early Middle Ages. The context in which the earlier introduction of the mouldboard plough should be understood is as yet far from clear. Our knowledge of the plough is still very inadequate and unevenly distributed in time and space, and the archaeological record relating to the cultivation systems of the Late Iron Age, AD 200-1050, is similarly very sporadic. It seems that the introduction of the plough was very likely associated with the significant changes that took place at the transition between the Early and Late Roman Iron Age, c. AD 200, and which characterised society in the subsequent centuries. The earlier introduction of the plough and of ridged- and/or flat-field systems of cultivation must have influenced the organisation of the infield and gradually rendered it impractical to move the settlement around within the resource area, as had been the case since the last centuries BC. Estimates of the percentage of cultivated land at different locations in Denmark show that some settlements must have had cultivated areas corresponding to those of Medieval times as early as the Germanic Iron Age, while other settlements had far smaller areas. This could be one of the reasons that some villages clearly became fixed at their present location already in Late Germanic Iron Age, and not exclusively at the transition between the Viking Age and Middle Ages, c. AD 900-1100, as was previously thought. There are a number of indications that the agrarian society of the Late Iron Age was increasingly able to generate a surplus, which could mobilise an ever more complex social structure: For example, the establishment of large, rich productive sites, especially in the 6th and 7th centuries AD, the founding of the earliest towns, such as Ribe, Aarhus and Hedeby in the 8th and 9th centuries, the emergence of regional kingdoms and the waging of several wars for resources in the period AD 200-600. The earlier introduction of the effective mouldboard plough fits well into this sequence of developments – as one of several significant factors. Lars Agersnap Larsen Viborg Museum